Super high flux microfiltration based on electrospun nanofibrous m-aramid membranes for water treatment - Yu, Jihye; Kim, Young-Gon; Kim, Dong Young; Lee, Sungho; Joh, Han-Ik; Jo, Seong Mu (POLYMER SOC KOREA, 2015)
The effects of ultrathin fibers using electrospun m-aramid nanofibrous membranes were evaluated to determine their performance as filters for water purification. The M150 membrane (average fiber diameter: 150 nm) was higher air-permeability than the M120 membrane (average fiber diameter: 120 nm). The commercial GSWP filter had much lower air-permeability than the electrospun membranes. The mean flow pore diameters of the electrospun membranes were much larger than the GSWP due to their high air permeabilities. Increased membrane thickness resulted in decreased airpermeability, mean pore size, and largest detected pore size. The M150 and M120 membranes with thickness of 10 mu m showed approximately 5 times higher water flux than the GSWP filter. However, these membranes surprisingly showed higher particle rejections (99.32% and 99.62%, respectively) in the filtration of 0.2-mu m PS latex particles compared with the GSWP filter (95.91%). This result indicates that highly branched, ultrafine fibrous structures of the m-aramid nanofibrous membranes contribute to the great increase in the particle rejection efficiency without loss of water flux (or airpermeability). From these results, the electrospun m-aramid nanofibrous membranes are expected to be used as a novel microfilter with a super high flux and high rejection efficiency.